Implication of Polycomb Members Bmi-1, Mel-18, and Hpc-2 in the Regulation of p16INK4a, p14ARF, h-TERT, and c-Myc Expression in Primary Breast Carcinomas - Silva, Javier; García, José M.; Peña, Cristina; García, Vanesa; Domínguez, Gemma; Suarez, Dolores; Camacho, Francisca I; Espinosa, Ruth; Provencio, Mariano; España, Pilar; Bonilla, Félix (My University, 2006)
Purpose: Deregulation of mammalian Polycomb group (PcG) members may contribute to human carcinogenesis. p16INK4a and p14ARF tumor suppressors, human telomerase reverse transcriptase (h-TERT), and oncoprotein c-Myc have been implicated in the regulation of the cell cycle and proliferation mediated by PcG proteins, mainly Bmi-1, in mice and in cell culture experiments. Here, we examine whether these in vitro findings can be extrapolated to the in vivo situation. Experimental Design:We measure the expression of PcG members Bmi-1, Mel-18, and Hpc-2 and their potential targets by reverse transcription-PCR, immunostaining, andWestern blotting in a series of 134 breast carcinomas and correlate the data with several clinical-pathologic variables of the tumors. Results: Expression of PcG genes was variably detected, but overexpression of Bmi-1 was the most frequent PcG alteration observed. In addition, statistical direct correlation in expression level of the three PcG members was detected. A correlation between c-Myc and Bmi-1 expression levels was observed; however, there was no correlation between expression of Bmi-1 and p16INK4a, p14ARF, or h-TERT. However, expression of the other PcG members Mel-18 and Hpc-2 correlated withthe cell cycle regulators. Moreover, PcG mRNA ^ altered expression correlated significantly withcertain clinical-pathologic variables associated withpoor prognosis. Conclusions: Our data suggest that the oncogenic role of Bmi-1 in human primary breast carcinomas is not determined by its capacity to inhibit INK4a/ARF proteins or to induce telomer ase activity